Optimization of Compressive Strength and Porosity of Mortars with Steel Scale by Grey Relational Analysis Method - Arici, Erdinc; Kelestemur, Oguzhan (Gazi Univ, 2021)
Various materials are added to the cement or concrete mixture in order to increase the quality of concrete in the construction sector. However, these materials sometimes improve some of the properties of concrete and some of its properties can be adversely affected. Numerous tests are needed to determine the effects of these additional materials on the concrete. However, this situation causes waste of time and material. In this study, the effects of the parameters on the compressive strength and porosity of the mortar samples with steel scale which is one of the waste materials of the iron and steel industry were investigated. Grey Relational Analysis (GRA) method was used to the optimization of these parameters. The four-parameter L16 orthogonal array was used to determine the experimental series. For this purpose, Mortar samples with different levels of fine scale, coarse scale, water/cement ratio and cement dosage were prepared and their compressive strength and porosity values were obtained. The data were evaluated by using Grey Relational Analysis method. As a result of the analysis, the optimum level of the parameters and the relationship between the compressive strength and porosity were determined.
Keywords: Grey Relational Analysis (GRA); steel scale; mortar; compressive strength; porosity